Molecular Cloning and Characterization of a Novel Dehydrin Gene from Ginkgo biloba. Issue 3 (18th August 2006) - Deng, Zhongxiang; Wang, Yiding; Jiang, Keji; Liu, Xuefen; Wu, Weisheng; Gao, Shi; Lin, Juan; Sun, Xiaofen; Tang, Kexuan
Abstract : A full-length cDNA encoding a dehydrin was cloned from the living fossil plant Ginkgo biloba by rapid amplification of cDNA ends (RACE). The cDNA, designated as GbDHN, was 813 bp long containing an open reading frame of 489 bp. The deduced GbDHN protein had 163 amino acid residues, which formed a 17 kDa polypeptide with a predicted isoelectric point (p I ) of 5.75. GbDHN had an S-segment and a K-segment, indicative of dehydrins, but no Y-segments. Homology analysis indicated that the S-segment and K-segment of GbDHN shared identity with those of other reported dehydrins, indicating that GbDHN belonged to dehydrin superfamily. Genomic sequence of GbDHN was also cloned using genomic walker technology. By comparing genomic DNA with the cDNA, it was found that there was a 257-bp intron in this gene. Promoter analysis indicated that it contained six CAAT boxes, one TATA box, one ABRE box and one GC-motif in the 5′-flanking region. Southern blot analysis revealed that GbDHN belonged to a single copy gene family. RT-PCR analysis revealed that GbDHN constitutively expressed in stems and roots. The increased expression of GbDHN was detected when G. biloba seedlings were treated with exogenous abscisic acid (ABA), salt stress and drought stress. These results indicate that the GbDHN has the potential to play a role in response to ABA and environmental stresses that can cause plant dehydration.